Macedo e o romance romântico - Volobuef, Karin [UNESP] (My University, 2013)
Joaquim Manuel de Macedo was a highly acclaimed writer among nineteenth - century readers, although posterity treated his work with many reservations. Despite the severity of his critics, Macedo’s contribution undeniably cannot be limited to his books, but extends to the very concept of the novel as a genre during Brazilian Romanticism. This novelistic concept is fueled by the observation of everyday life as well as by aesthetic ideas brought to light by European Romanticism. Differently, however, in A luneta mágica [The Magic Looking Glass] Macedo employed aspects of the fantastic to produce a daringly critical and creative novel that contrasts vividly with other Romantic works in Brazil

Joaquim Manuel de Macedo foi um escritor que gozou de enorme sucesso junto ao público do séc. XIX; já a posteridade tratou sua obra com muitas reservas. A despeito dessa severidade dos críticos, é inegável que a contribuição de Macedo não se restringe às suas obras em si, mas estende-se à própria concepção de romance durante o Romantismo brasileiro. Essa concepção é carregada de observação do dia-a-dia e de uma estética amparada em elementos do Romantismo europeu. Em A luneta mágica, ao contrário, Macedo explora os veios fantástico e maravilhoso, mostrando ousadia crítica e criativa, motivo pelo qual o romance contrasta vivamente com as outras produções românticas no Brasil
Macedo and the romantic novel
Keywords: Joaquim Manuel de Macedo; A luneta mágica; A Moreninha; Joaquim Manuel de Macedo; A luneta mágica; A Moreninha